Fish oil omega-3 fatty acids partially prevent lipid-induced insulin resistance in human skeletal muscle without limiting acylcarnitine accumulation - Stephens, Francis B.; Mendis, Buddhike; Shannon, Chris E.; Cooper, Scott; Ortori, Catharine A.; Barrett, David A.; Mansell, Peter; Tsintzas, Kostas (Portland Press, 2014)
Acylcarnitine accumulation in skeletal muscle and plasma has been observed in numerous models of mitochondrial lipid overload and insulin resistance. Fish oil n3PUFA (omega-3 polyunsaturated fatty acids) are thought to protect against lipid-induced insulin resistance. The present study tested the hypothesis that the addition of n3PUFA to an intravenous lipid emulsion would limit muscle acylcarnitine accumulation and reduce the inhibitory effect of lipid overload on insulin action. On three occasions, six healthy young men underwent a 6-h euglycaemic–hyperinsulinaemic clamp accompanied by intravenous infusion of saline (Control), 10% Intralipid® [n6PUFA (omega-6 polyunsaturated fatty acids)] or 10% Intralipid®+10% Omegaven® (2:1; n3PUFA). The decline in insulin-stimulated whole-body glucose infusion rate, muscle PDCa (pyruvate dehydrogenase complex activation) and glycogen storage associated with n6PUFA compared with Control was prevented with n3PUFA. Muscle acetyl-CoA accumulation was greater following n6PUFA compared with Control and n3PUFA, suggesting that mitochondrial lipid overload was responsible for the lower insulin action observed. Despite these favourable metabolic effects of n3PUFA, accumulation of total muscle acylcarnitine was not attenuated when compared with n6PUFA. These findings demonstrate that n3PUFA exert beneficial effects on insulin-stimulated skeletal muscle glucose storage and oxidation independently of total acylcarnitine accumulation, which does not always reflect mitochondrial lipid overload.